2011
DOI: 10.1038/onc.2011.4
|View full text |Cite
|
Sign up to set email alerts
|

Homeodomain protein DLX4 counteracts key transcriptional control mechanisms of the TGF-β cytostatic program and blocks the antiproliferative effect of TGF-β

Abstract: The anti-proliferative activity of transforming growth factor-β (TGF-β) is essential for maintaining normal tissue homeostasis and is lost in many types of tumors. Gene responses that are central to the TGF-β cytostatic program include activation of the cyclin-dependent kinase inhibitors p15Ink4B and p21WAF1/Cip1 and repression of c-myc. These gene responses are tightly regulated by a repertoire of transcription factors that include Smad proteins and Sp1. The DLX4 homeobox patterning gene encodes a transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 49 publications
(101 reference statements)
2
52
0
Order By: Relevance
“…This induction occurs by two mechanisms. We identified that DLX4 prevents transforming growth factor-TGF--mediated repression of c-myc transcription, and also induces c-myc promoter activity independently of TGF-/Smad signaling (Trinh et al, 2011). DLX5, another member of the DLX family, has also been found to directly activate c-myc transcription in lung cancer cells (Xu and Testa, 2009).…”
Section: Sustained Proliferative Signalingmentioning
confidence: 94%
See 3 more Smart Citations
“…This induction occurs by two mechanisms. We identified that DLX4 prevents transforming growth factor-TGF--mediated repression of c-myc transcription, and also induces c-myc promoter activity independently of TGF-/Smad signaling (Trinh et al, 2011). DLX5, another member of the DLX family, has also been found to directly activate c-myc transcription in lung cancer cells (Xu and Testa, 2009).…”
Section: Sustained Proliferative Signalingmentioning
confidence: 94%
“…We have found that overexpression of DLX4 in ovarian cancer cells induces FGF-2 expression, increases clonogenicity in vitro and promotes tumor growth in vivo (Hara et al, 2007), but it is not known whether DLX4 directly activates FGF-2 transcription. We recently found that DLX4 also induces expression of c-Myc (Trinh et al, 2011). This induction occurs by two mechanisms.…”
Section: Sustained Proliferative Signalingmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, BP1 inhibits TGF-β-mediated induction of p15 Ink4B and p21 WAF1/Cip1 expression by blocking the TGF-β/Smad signaling pathway in normal and malignant epithelial cell lines [53].…”
Section: Brca1mentioning
confidence: 99%